Pengaruh variasi formula semi solid natrium diklofenak terhadap absorpsiperkutan dan korelasinya secara in vitro - in vivo - Mae Sri Hartati W Mae Sri Hartati W (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Diclofenac sodium is a nonsteroidal antiinflammatory drug (NSAID), which is drug of choice for rheumatoid arthritis. It is commercially available as enteric coated tablet and emulgel for topical dosage form.Topical drug was prepared and developed for systemic purposes in the treatment of rheumatoid arthritis, to reduce the risk of adverse drug reaction given orally. As an oral antirheumatoid drug, it caused dizziness and irritation on gastric mucosa.The study was carried out to assess the effect of semisolid formulation variation on its percutaneous absorption. The experiment was performed by preparing 4 formulas of ointment i.e. hydrocarbon base, washable base, 0/W emulsion base, W/O emulsion base and commercial cream E as a control drug. All of the formulas and standard cream were tested in vitro for the rate of dissolution and its percutaneous absorption on rabbits.The Dissolution Efficiency (DE) of washable emulsion, 0/W emulsion base,- and the commercial cream was correlated with their Ka from the experiment of percutaneous absorption. Among the three formulas, the C ointment (0/W emulsion base) showed the best correlation. The order of the correlation declined as follows C, B and E. From the result it can be concluded that the change of formulation could affect the dissolution and in turn could affect the absorption of the active compounds.Key words : ointment - cream - diclofenac - in vitro - in vivo